ANALISA KESIAPSIAGAAN DALAM PENGURANGAN RISIKO BENCANA TERHADAP ANCAMAN BANJIR DI DESA RANTAU PAKAM DAN TELUK KEPAYANG, KECAMATAN BENDAHARA, KABUPATEN ACEH TAMIANG, PROVINSI ACEH - Marzuki, Ismail (Jurnal Spasial, 2026)
Aceh Tamiang Regency is an area with a high level of flood hazard, experiencing major flood events in 1996, 2006, 2018, 2020, 2021, 2022, and 2023, which have caused substantial impacts on social, economic, and infrastructure sectors. The increasing frequency and intensity of these flood events have prompted this study to analyze community knowledge, evaluate preparedness actions undertaken by local communities, and formulate an appropriate preparedness model for flood disaster risk reduction. This study employed a qualitative approach through focus group discussions with key informants, data triangulation, field observations, and analysis of relevant documents. Data were analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that Rantau Pakam Village demonstrates stronger preparedness knowledge and practices than Teluk Kepayang Village. This advantage is attributed to the availability of a more effective early warning system, contingency planning documents, a disaster-resilient village team, preparedness facilities, and experience in conducting disaster simulations involving vulnerable groups. In contrast, although Teluk Kepayang Village has preparedness facilities and participates in the sister village mechanism, it lacks a structured preparedness management system. The study concludes that community preparedness is strongly influenced by institutional support, the quality of program interventions, and inter-village collaboration, which collectively enhance disaster risk reduction knowledge and practices. An integrated preparedness model combining anticipatory actions and the sister village mechanism is recommended as an effective approach for addressing flood hazards in disaster-prone areas such as Bendahara District.